(untitled) (Biological Sciences - PJSIR, 1994)
The com-flour feed varieties commonly consumed in Nigeria were fortified with dry white crayfish (Pinnens notialis), red crayfish (Macrobrachiummacrobium) and Tilapia. Eight different brands of popular infant formulae and the fortified com meals were analysed for fats, protein, carbohydrates and nutritionally valuable minerals. Results obtained showed low fat, protein and carbohydrate values in the com flour infant meal. However, on fortification, corn- flour meal -crayfish blends (4: 1) compared favourable well with commercial infant formulae in terms of the fat, protein, carbohydrate and mineral elements. These results including the cost analysis of the fortified meal vis-a-vis the commercial infant feeds were discussed.